A neuropsychoanalytic understanding and treatment for a borderline patient who used cannabis. Issue 1 (2nd January 2017) - Flores Mosri, Daniela
Abstract : Borderline pathology is one of the most frequent diagnoses in psychoanalytic practice. Its features are different from a psychiatric point of view and from a psychoanalytic one. The deep psychic pain present from an affective perspective does not always match the symptomatic character features commonly related to this organization. The pain comes from a narcissistic injury, causing the presence of latent depression, vague anxiety and anaclitic object relations, all related to anxiety about object loss. These psychodynamic features can contribute to an addictive vulnerability that frequently recruits cannabis as its chosen drug because of its neurobiological impact on the psychological functioning of the patient, of which he is usually unaware. This paper aims to describe the neuropsychodynamic understanding of a borderline patient who used cannabis to deal with pain derived from a narcissistic injury that exceeded his capacity to use purely psychological defenses, forcing him to look for external ones provided by this drug. The hypotheses presented in this paper come from case study material that used a neuropsychoanalytic integration to modify the technique applied in the treatment. Psychoanalysis provides helpful hypotheses for working with these patients, who deserve the best treatment possible for the intense psychic pain that drives them to engage in self-destruction while trying to feel better. Because of the neurochemical modifications induced in the patient, treatment can be better understood from a neuropsychoanalytic point of view. More research is needed to better refine our theoretical models and treatment of these difficulties.